Quantitative conversion of free, acid-hydrolyzable, and bound ellagic acid in walnut kernels during baking. (30th January 2023) - Guo, Xin; Gu, Fengying; Yang, Tingting; Shao, Zhixiao; Zhang, Qiaozhen; Zhu, Jinjin; Wang, Feng
Graphical abstract: Highlights: Baking promoted the conversion of ellagitannins to ellagic acid in walnut kernels. The EAC in FPA increased by 99.52% after baking at 165 °C for 30 min. The ellagitannins in AHPA contributed over 60% to the increase of EAC in FPA. The ETC in AHPA was determined by the "subtraction method" for the first time. Eight ellagitannins were the main precursors of ellagic acid in walnut kernels. Abstract: Ellagitannins, the main components of walnut kernel polyphenols, are easily degraded by heating to produce ellagic acid, precursor in the production of urolithins that show multiple physiological functions. To analyze the conversion of ellagitannins to free ellagic acid in walnut kernels during baking, a quantitative method was developed to investigate the ellagic acid content (EAC) in free phenolic acid (FPA), acid-hydrolyzable phenolic acid (AHPA), and bound phenolic acid (BPA) fractions. The results showed that the EAC in FPA reached its maximum (5.17 ± 0.30 mg/g DW) after baking at 165 °C for 30 min, which increased by 99.52% compared with the control. Meanwhile, the content of ellagitannins (ETC) in AHPA and BPA dropped by 89.14% and 26.08%, respectively. It suggested that baking promoted the conversion of ellagitannins in AHPA and BPA to ellagic acid in FPA. Eight ellagitannins were regarded as the main precursors of ellagic acid in walnut kernels.